Attitudes to remote patient monitoring among orthodontists in Ireland - a qualitative study - Donnelly, Michael (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2023)
Aims: The aim of the study was to explore the attitudes to remote patient monitoring among orthodontists in Ireland. Methods: A descriptive, qualitative study was conducted involving a purposive sample of orthodontists working in private and public orthodontic practices across Ireland. A topic guide was developed. Six focus groups and a single interview involving 16 participants were undertaken. Semi-structured interviews were audio-recorded and transcribed verbatim with Sonix TM software. A thematic analysis approach was carried out for data analysis using MAXQDA TM software. Results and Discussion: Following data analysis, seven main themes were identified. Factors influencing adoption of RPM include patient-driven factors, peer influence, settings/systems, cost-effectiveness, clinical applications, misuse and oversight, attitude for potential adoption of RPM technology. These factors were found to exert important roles as influencers, barriers or both. Orthodontists anticipate broad adoption of RPM technologies in the future allied with an increased array of applications and available technologies. An increased acceptance and penetration of RPM was acknowledged; however, not all non-user participants would be willing to embrace this. Users of RPM technology have a positive attitude towards RPM technology whilst non-users have ambivalent attitudes. Users positively perceive a positive influence of RPM on their practices through increased efficiency, broad usage, financial and time savings. Non-users perceive lack of patient desire, fixed appliances, public orthodontic setting, cost, time, public perception of profession as barriers. Remote monitoring of oral hygiene of patients with fixed appliances may become imbedded into routine care Conclusions: This qualitative study highlights the multifaceted nature of RPM as perceived by the participants with a range of facilitators and barriers identified.
APPROVED
Keywords: Remote patient monitoring; Orthodontics; Qualitative